The Application of Conjugate Gradient Methods to Optimize 3D Printed Parameters - Nurul Hajar; Nurul ‘Aini; Norrlaili Shapiee; Mohd Rivaie; Adam Samsudin; Nor Hafizah Hussin; Siti Haryanti Hairol Anuar (Semarak Ilmu Publishing, 2024)
Indexed by Scopus